ODPOWIEDZIALNOŚĆ UBEZPIECZYCIELA W UBEZPIECZENIU OC P OSIADACZY POJAZDÓW MECHANICZNYCH NA TLE ORZECZNICTWA SĄDOWEGO - Fuchs, Dariusz (Zeszyty Prawnicze, 2017)
The Insurer’s Liability in a Civil Liability Insurance of Mechanic Vehicles in the Light of Courts’ Judgements Summary The article presents the verdicts of the com m on courts regarding the scope of the insurer’s liability in a civil liability insurance of mechanic vehicles. At the same time an attention is drawn to the relationship of the insurer’s liability as being of an accessorial and guarantee nature and the liability of the perpetrator of the accident - the insured. The article also contains comparative remarks, including in particular the jurisprudence of English courts. At the same time the attention was drawn to the legal limitations of the insurer’s liability, above all on the basis of the act on the obligatory insurance o f 2003. The analysis also concern the relationship between relevant provisions of the insurance activity and the act on the obligatory insurance. Finally, the particularity of the regulation regarding the time scope of the insurer’s liability. The author positively evaluates the regulatory environment de lege lata, however, he also indicates proposals for possible amendments.